Reseña/Review (Serres, M., "Pulgarcita", Barcelona: Gedisa, ISBN: 9788497847964, 125 págs., 2014) - De León-Escribano, Rosa Mariana (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2014)
Reseña/Review (Serres, M., "Pulgarcita", Barcelona: Gedisa, ISBN: 9788497847964, 125 págs., 2014)